Alphaherpesvirus Major Tegument Protein VP22: Its Precise Function in the Viral Life Cycle - Wu, Liping; Cheng, Anchun; Wang, Mingshu; Jia, Renyong; Yang, Qiao; Wu, Ying; Zhu, Dekang; Zhao, Xinxin; Chen, Shun; Liu, Mafeng; Zhang, Shaqiu; Ou, Xuming; et al. (Frontiers in Microbiology, 2020)
Alphaherpesviruses are zoonotic pathogens that can cause a variety of diseases in humans and animals and severely damage health. Alphaherpesvirus infection is a slow and orderly process that can lie dormant for the lifetime of the host but may be reactivated when the immune system is compromised. All alphaherpesviruses feature a protein layer called the tegument that lies between the capsid and the envelope. Virus protein (VP) 22 is one of the most highly expressed tegument proteins; there are more than 2,000 copies of this protein in each viral particle. VP22 can interact with viral proteins, cellular proteins, and chromatin, and these interactions play important roles. This review summarizes the latest literature and discusses the roles of VP22 in viral gene transcription, protein synthesis, virion assembly, and viral cell-to-cell spread with the purpose of enhancing understanding of the life cycle of herpesviruses and other pathogens in host cells. The molecular interaction information herein provides important reference data.